Hukum di Era Post Truth - Asmarita; Mustar; Surya Sukti (PT. Hasba Edukasi Mandiri, 2025)
Post-truth describes a situation where (objective) facts are no longer relevant, especially in today's society, this is because personal beliefs and feelings have more influence in forming public opinion than objective facts. This study discusses how law enforcement in the post-truth era, and the results of the study show that it can use a philosophical way of thinking.